Oestrogen and progesterone receptors in chick oviduct chromatin after administration of oestradiol, progesterone or anti-oestrogen. - Lebeau, M C (1982)
Oestrogen-primed and withdrawn chicks were injected with oestradiol benzoate, progesterone, and/or the anti-oestrogens tamoxifen and 4-hydroxytamoxifen. Oestrogen receptors were studied in oviduct chromatin solubilized by mild digestion of purified nuclei with micrococcal nuclease. After a single injection of oestradiol benzoate, ultracentrifugation on sucrose gradients of chromatin extracts labelled with [3H]-oestradiol showed two peaks of oestradiol binding sites, sedimenting at 13--14 S and 7--8 S. After repeated injections of oestradiol benzoate, the 13--14 S peak increased more than the 7--8 S peak. After injection of anti-oestrogen alone or together with oestradiol benzoate, no [3H]oestradiol-binding or 4-hydroxy[3H]tamoxifen-binding peaks were detected in the chromatin. Injection of progesterone also produced an increase of the 13--14 S and 7--8 S chromatin oestradiol receptor. Progesterone receptor could only by detected in chromatin early after progesterone administration, and it sedimented in density gradients with the 12 S mononucleosome fraction. Tamoxifen injected together with progesterone gave higher levels of 13--14 S oestrogen binding sites than did progesterone alone. The presence of a 13--14 S peak of oestrogen binding sites in hormonal situations which promote a biological response in the chick oviduct, and the absence of this peak after administration of anti-oestrogens, suggest that this subfraction of chromatin contains elements involved in gene regulation.